Ocean Black - Bostrom, Hank (New York Kensington Pub. Corp., 1995)
18,000 FEET BELOW THE SURFACE OF THE PACIFIC, BILLIONAIRE INDUSTRIALIST PAUL DERIDE HAS HIT A MOTHERLODE OF MANGANESE. BUT THE ONLY WAY TO RETRIEVE THE PRECIOUS ORE IS THROUGH A SERIES OF STRATEGICALLY PLACED NUCLEAR DETONATORS THAT COULD TRIGGER A MASSIVE EARTHQUAKE ALONG CALIFORNIA'S SAN ANDREAS FAULT.
Keywords: Illinois--Chicago -- Missing children -- Domestic fiction